Patterns as Abstractions of Spatial Axes - Gulden, Jens (Electronic Communications of the EASST, 2010)
The decision of how to model patterns as elements of formal systems isa yet sparsely covered research topic. The present article introduces an approach which understands patterns as non-linguistic carriers of formal semantics in models. The notion of patterns is embedded into a theory which links spatial orientation and navigation to the constitution of semantics in human understanding. Inside this framework, the concept of patterns is treated conform to the notion of spatial axes on a shared higher level of abstraction. A formal model is presented which expresses the introduced notion of patterns in a practically applicable meta-modeling language.